Bibliometric Analysis to Understand the Place of the Visits of Natural Areas in the Field of Volunteered Geographic Information Research - Robin Lesné; Marc Langenbach; Pascal Mao; Hugues François; Nicolas Robinet (Revue de Géographie Alpine)
A growing and massive digitalisation of society marks the visits of natural areas. This leads to the production and sharing of digital footprints which, as soon as they contain data allowing them to be spatialised, become Volunteered Geographic Information (VGI). By making it possible to understand phenomena that are difficult to observe, their use opens new research perspectives, even more for mountain areas marked by the need to understand these visits and by the lack of efficiency of other systems. Documenting the phenomenon of VGI within scientific production can therefore help to lay the foundations for future research. Our aim is to provide a comprehensive understanding of the academic literature on VGI. We conduct a bibliometric analysis based on a scoping study of the 1,001 papers listed on the Web of Science dealing with VGI. Firstly, we identify the evolution of their production since 2009 and their particularly important attachment to geography and formal sciences. Secondly, we highlight trends in their production context, including the influence of Geographic Information Sciences in the authorship and dissemination spaces of the work, and the dominance of a few countries in the production of this literature. Thirdly, we identify themes that are prevalent in the corpus through an analysis of keywords, and the lacunar nature of the issue of recreational use of natural areas. Thus, our paper highlights the maturity of the field of studies of VGI, but also the opportunity that is emerging in terms of mobilising this tool in scientific work dealing with the visits and management of natural areas.